PENGARUH PENGUASAAN KOSAKATA DAN TATA BAHASA TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPTIF BAHASA INGGRIS - Jennifer Aster Visakha (Universitas Indraprasta PGRI, 2019)
This research aims to know, analyze and examine the truth of the hypothesis on the effects of vocabulary and grammar mastery towards the skill of students of state senior high schools in Tangerang Regency, Banten Province, in writing English descriptive texts. The research employed a survey method. The results of the research are: (1) There are significant effects of vocabulary and grammar mastery collectively towards the skill of students of state senior high schools in Tangerang Regency, Banten Province in writing English descriptive texts. It is proved by Sig. 0.000 < 0.05 and Fobserved160.498. (2) There is a significant effect of vocabulary mastery partially towards the skill of students of state senior high schools in Tangerang Regency, Banten Province, in writing English descriptive texts. It is proved by Sig. 0.000 < 0.05 and t observed 5.396. 3) There is a significant effect of grammar mastery partially towards the skill of students of state senior high schools in Tangerang Regency, Banten Province, in writing English descriptive texts. It is proved by Sig. 0.000 < 0.05 and t observed 9.241. This current research results show that the students’ skills in writing English descriptive texts are strongly influenced by their vocabulary and grammar mastery. Therefore, teachers of the state senior high schools should be active in improving the students’ vocabulary and grammar mastery through creating guided learning and up-to-date learning methods. The teachers also need to give the students motivation, assistance dan periodical review to continuously practice enriching their vocabulary, improving their grammar and skill in writing English descriptive texts. Key Words: descriptive text; foreign language writing; vocabulary mastery; grammar mastery.